Biological properties of hypoxia-related gene expression models/signatures on clinical benefit of anti-EGFR treatment in two head and neck cancer window-of-opportunity trials. (March 2022) - Lenoci, Deborah; Carenzo, Andrea; Cavalieri, Stefano; Pistore, Federico; Serafini, Mara Serena; Bossi, Paolo; Schmitz, Sandra; Machiels, Jean-Pascal; Licitra, Lisa Francesca; De Cecco, Loris
Highlights: Biomarkers are analyzed in two WOO anti-EGFR studies on pre- and post-treatment HNSCC tumors. In pre treatment samples, hypoxia signatures positively associated with PET response to anti-EGFR. In pre treatment samples, hypoxia traits were negatively correlated to the immunoscore. Signature's down-modulation in post-treatment samples confirmed the anti-EGFR activity.